2019
DOI: 10.1016/j.cub.2019.02.022
|View full text |Cite
|
Sign up to set email alerts
|

The Lateral Root Cap Acts as an Auxin Sink that Controls Meristem Size

Abstract: Highlights d Cytokinin acts in the LRC to coordinate cell differentiation of the root meristem d Cytokinin controls auxin levels via PIN5 and GH3.17 to trigger cell differentiation d PIN5 and GH3.17 control auxin levels specifically in the LRC d LRC serves as an auxin sink which controls meristem size thus organ growth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 49 publications
0
75
0
Order By: Relevance
“…Its position is controlled by regulatory balance of auxin and cytokinine [45], which positions the auxin minimum [47] initiating the cell elongation (i.e., the differentiation). The regulation of auxin accumulation, and its degradation through ARR1 signaling, is dependent on PIN5 and GH3.17 genes [48]. A shortened meristematic zone with rapid transition from basal portion of proliferation domain into transition domain is one of developmental possibilities that lead to shorter primary root in ahl18.…”
Section: Root Apical Meristem and Ahl18mentioning
confidence: 99%
“…Its position is controlled by regulatory balance of auxin and cytokinine [45], which positions the auxin minimum [47] initiating the cell elongation (i.e., the differentiation). The regulation of auxin accumulation, and its degradation through ARR1 signaling, is dependent on PIN5 and GH3.17 genes [48]. A shortened meristematic zone with rapid transition from basal portion of proliferation domain into transition domain is one of developmental possibilities that lead to shorter primary root in ahl18.…”
Section: Root Apical Meristem and Ahl18mentioning
confidence: 99%
“…Our results show increases in both PIN3 and LAX1 proteins in auxin‐treated seedlings (average ratio values 1.66 and 1.95, respectively, Figure D), which are consistent with previously reported expression data from imaging proPIN3::PIN3‐GFP lines and ProLAX1:GUS reporter lines . It has also recently been shown that GH3.17 protein levels are crucial for maintenance of auxin levels in root meristems, suggesting that there may be positive feedback regulation on this protein regulate auxin homeostasis.…”
mentioning
confidence: 99%
“…Based on our data, we do not exclude the role of EXPA1 in the control of RAM size, but probably in a concert with other EXPAs and dominantly in the columella/LRC (vide infra). The role of (cytokinin-regulated) auxin accumulation in the LRC in the control of RAM size has been proposed recently (Di Mambro et al, 2019). However, even in case of more distinct transcriptional regulation of EXPA1 by NAA, we do not see any significant and consistent EXPA1 upregulation in the LRC, both at the level of promoter activity or EXPA1 protein (data not shown), thus leaving the functional importance of cytokinin-and auxin-mediated regulation over EXPA1 in the root tip rather unclear.…”
Section: Discussionmentioning
confidence: 99%